EVOLUTION AND QUALITY OF FINANCIAL REPORTING IN ROMANIA: AN OVERVIEW FROM 1990 TO PRESENT - NICHITA Mirela (Annals of the University of Oradea: Economic Science, 2015)
The results of a business activity are concentrated in the financial reports; accounting is the instrument that provides these reports to internal and external users in order to help users to make useful economic decisions. At international level, the accounting is standardized by IASB (former IASC) which elaborate financial reporting standards (known as IAS / IFRS) in order to improve the quality and transparency of reporting. The changes in business environment (globalization, mergers and acquisition transactions, internationalization, corporate social implications) requires a continuous updated of financial reporting. The accounting information is useful to their users if comply with quality characteristics, defined through the Conceptual Framework of Financial Reporting issued by IASB (the new form of Conceptual Framework is in place starting 2010). Starting 1990, the researchers (namely academics) had to focus on new kind of works about accounting and accounting research; the process was difficult and is not end. Initially, the academics inspired from French accounting books and translated them with some changes/improvements correlated to Romanian economy. Gradually, some journals founded and the academics and practitioners begin to publish their work in a more scientific manner. In this paper, we will try to present an evolution of financial reporting in Romania, to identify if the alignment to international financial reporting standards improved the quality of reporting, and to investigate whether the adoption of the International Financial Reporting Standards for the individual financial statements of Romanian listed entities has improved the value relevance of the accounting numbers. The study uses data of entities listed on the Bucharest Stock Exchange, prior and post the adoption of the International Financial Reporting Standards for the individual financial statements. The year 2012 represents the year in which Romanian entities listed on the regulated market had to prepare their individual financial statements in accordance with the International Financial Reporting Standards. Due to the fact that the analysis aims to capture the quality ante and post the adoption of IFRS for individual financial statements, this analysis is conducted on a five-year period of time, namely between 2009 and 2013. The year 2011 is the year prior to the one in which entities had to prepare their individual financial statements in accordance to IFRS, and the year 2013 represents the second year of reporting accordingly IFRS requirements.